2020
DOI: 10.1016/j.foodhyd.2019.105345
|View full text |Cite
|
Sign up to set email alerts
|

Generality and specificity of the binding behaviour of lysozyme with pectin varying in local charge density and overall charge

Abstract: We examined the similarities and differences of the binding behavior of lysozyme (lys) with pectin varying in local charge density (blockwise distribution and statistical distribution of methoxyl groups, BP and SP) and similar degree of methoxylation (DM). The interaction at ionic strength I=0.01 and pH 5.1 was found to be mainly electrostatic, associated with an exothermic enthalpy change. BP which is more inclined to self-association binds lys forming strongly associated complex particles with average sizes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 62 publications
1
14
1
Order By: Relevance
“…Unlike the results of Girard et al ., 23 P29 and P90 behaved differently with PA in the ITC studies. The ΔH and ΔS values were lower for PA‐P29 than PA‐P90 (Table 1).…”
Section: Resultscontrasting
confidence: 99%
See 3 more Smart Citations
“…Unlike the results of Girard et al ., 23 P29 and P90 behaved differently with PA in the ITC studies. The ΔH and ΔS values were lower for PA‐P29 than PA‐P90 (Table 1).…”
Section: Resultscontrasting
confidence: 99%
“…Note that the K value is higher for PA‐P29 admixtures (P29 with higher GalA content) than PA‐P90. This was previously observed in ovalbumin‐CMC 25 and in a β ‐lactoglobulin‐pectin 23 system. The impact of DB on the thermodynamic parameters is better understood by comparing the current study with the previously reported pea protein isolate (PPI)‐pectin interaction by Lan et al .…”
Section: Resultssupporting
confidence: 79%
See 2 more Smart Citations
“…The entropy gain (Δ S ) from the release of counterions and water can even overcome the enthalpic contribution of electrostatic interaction. However, in some protein/polysaccharide systems, enthalpy change (Δ H ) was more dominant. Therefore, we determine the thermodynamics of β-CG/LYS complexation using isothermal titration calorimetry (ITC) to understand the balance between Δ S and Δ H during HPCC and the thermodynamic nature behind β-CG/LYS interaction (Figure ).…”
Section: Resultsmentioning
confidence: 99%